Sunscreen from Coconut Coir Based Lignin Nanoparticles with Extraction Method and pH Shifting as an Anti-UV Material - Sari, Diana Novita; Anggerta, Lintang Alivia; Alfiana, Aulia Firda (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2023)
Indonesia is a tropical country located on the equator with high sun exposure, so sunscreen is needed to reduce the risk of exposure to ultraviolet (UV) light. In this research, a sunscreen was developed that uses natural active ingredients in the form of lignin made from coconut coir. The aim of this research is to determine the comparison between the mass of coconut coir and the volume of ethanol solution that produces the highest lignin content, as well as the concentration comparison between lignin nanoparticles and commercial sunscreen that produces the highest SPF value. The synthesis of lignin from coconut coir was carried out using an extraction method using ethanol solvent, followed by a hydrolysis process with NaOH and acidification with H2SO4, while lignin nanoparticles were made using a pH shifting method using ammonia and HCl. The lignin nanoparticles formed are then added to the sunscreen's active ingredient. The variables used were the ratio of the mass of coconut coir to the volume of 80% ethanol solvent (1:5, 1:10, 1:15, and 1:20 (w-v)) and the concentration of lignin in commercial sunscreen cream (2%, 4%, 6%, 8%, and 10% (w-w)). The results of the research show that the higher the solvent ratio, the more lignin is produced, but will decrease after reaching the optimum point. The optimal solvent volume occurs at a ratio of 1:15 (w-v) with a yield of 12.94% (w-w). In addition, the higher the lignin concentration, the resulting SPF value will also increase. The best concentration is 10% (w-w) at a solvent ratio of 1:15 (w-v) with an SPF value of 22.23.